Measuring Maslahah on Collateral Implementation in Mudaraba Contract at Sharia Banking - Dini Maulana Lestari; Abdul Qoyum (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2021)
This research aims to measure maslahah level on collateral implementation in mudaraba financing contract at sharia banking. This is important, because although the existence of collateral in the contract is able to create such maslahah, but there is no specific level regarding to it. Then, this research also tries to examine the relationship between collateral to maslahah itself in order to know the effect which give by those variables. This is an explanatory research uses a quantitative approach with survey method. This research also uses descriptive statistic and path analysis method by IBM SPSS Statistic 22 in order to reach the purpose of this research. This research picked sharia banking practitioners and customers specifically in Cirebon as the population, reaching 116 respondent which used as the sample of research. The result of this research reported that the implementation of collateral in mudaraba financing contract is truly provide maslahah level both for sharia banking practitioners and customers. This result was also strengthened by the direct effect between each variable which revealed a positive significant effect.